Effectiveness Of Conventional Periodontal Treatment With Tetracycline Fiber Versus Minocycline Gel Application Subgingivally In Periodontitis Patients - Siti Lailatul Akmar Zainuddin; Norjehan Latib; Haslina Taib; Basaruddin Ahmad; Muhammad Annurdin Sabarudin; Wan Majdiah Wan Mohamad (Springer Nature, 2024)
Indexed by WOS